Fiscal policy and interest rates in a small open economy - Jesper Lindé (Sveriges Riksbank, 2000)
This paper contains an empirical investigation of the effects of fiscal policy on interest rates based on a conventional stochastic macro model designed for a small open economy. The empirical investigation undertaken utilizes data for Sweden, a country which has experienced very large fluctuations in the government budget deficits and in the short- and long-term nominal interest rates, thus providing a better empirical test than previous studies. According to the empirical results, larger budget deficits jspell higher interest rates, as posited by conventional macroeconomic theory.
Keywords: E12; E62; F41; 330; Term structure of interest rates; Ricardian equivalence; budget deficits; small open economy; stationary and non-stationary time series